East Java Growth Diagnostic : Identifying the Constraints to Inclusive Growth in Indonesia's Second-Largest Province - World Bank (World Bank, Jakarta, 2017)
East Java is the second largest contributor to Indonesia's economy with a growth rate similar to national level and other major provinces in Java. Nevertheless, for a province that is expected to be a major economic center in the country, there has been very little change in the region's economic structure in the past 10 years. Since 1995, the share of industry and agriculture in the economy is almost unchanged. Furthermore, the growth in both of these two sectors has been low, despite the fact that industry was once the main driver of the East Java economy. This report analyzing the economic conditions of East Java shows that the province offer many economic advantages for investors, such as its geographical location, adequate credit facilities, an abundant and competitively priced workforce, conducive security conditions, and an overall robust macroeconomic condition. The report also finds a number of constraints that, if prioritized and effectively addressed, could boost East java's growth rate to higher level. The main binding constraints to growth in East Java are infrastructure, particularly related to business operations, and the business climate.